2015
DOI: 10.15361/1984-5529.2015v43n1p84-92
|View full text |Cite
|
Sign up to set email alerts
|

Single-head broccoli response to nitrogen application

Abstract: Information regarding nitrogenous fertilization in broccoli for Santa Catarina is still scarce. Therefore, this study aimed at analyzing the nitrogen effect upon the levels of chlorophyll (a, b and total), carotenoids and nitrogen (N) forms in leaves, and upon the yield of inflorescence, stem and leaves of singlehead broccoli. The experiment was conducted in September, 2011, in Florianópolis (SC), with seedlings of single-head broccoli (BRO 68 -Syngenta), in completely randomized blocks, with five treatments (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…A similar response was reported by Dufault (1988) in broccolis plants growing in green house and by Arjona and Greig (1984) in broccolis cultivar Green Comet, with a detected increase in chlorophyll content. Ambrosini et al (2015) also reported that for the broccoli cultivar BRO 68, nitrogen application stimulated the synthesis of chlorophyll in the leaves, resulting in improved nutritional quality.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…A similar response was reported by Dufault (1988) in broccolis plants growing in green house and by Arjona and Greig (1984) in broccolis cultivar Green Comet, with a detected increase in chlorophyll content. Ambrosini et al (2015) also reported that for the broccoli cultivar BRO 68, nitrogen application stimulated the synthesis of chlorophyll in the leaves, resulting in improved nutritional quality.…”
Section: Resultsmentioning
confidence: 94%
“…Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License indicated that nutrients have important effects on broccolis productivity and quality (Belec et al, 2001;Moniruzzaman et al, 2007;Ambrosini et al, 2015).…”
Section: Introductionmentioning
confidence: 92%
“…On the other hand, leaf P and Ca concentrations had a quadratic effect in response to N rate, and the maximum concentration of P (12.0 g kg -1 ) and Ca (37.3 g kg -1 ) was obtained with the application of 194 and 268 mg N kg -1 , respectively ( Figures 2B and 2D). The significant increase in macronutrient concentration in the leafy vegetable leaves in response to application rates between 170 and 210 mg kg -1 of N has been commonly reported under protected cultivation conditions (ZANÃO JÚNIOR et al, 2005;KANO et al, 2010;AMBROSINI et al, 2015). Table 3.…”
Section: Nitrogen Sources Number Of Leaves Per Plant Leaves Fresh Massmentioning
confidence: 88%